A New Reversed Version of a Generalized Sharp Hölder's Inequality and Its Applications - Jingfeng Tian; Xi-Mei Hu (Abstract and Applied Analysis)
We present a new reversed version of a generalized sharp Hölder's inequality which is due to Wu and then give a new refinement of Hölder's inequality. Moreover, the obtained result is used to improve the well-known Popoviciu-Vasić inequality. Finally, we establish the time scales version of Beckenbach-type inequality.